Swelling behaviors and characterization of oil palm empty fruit bunch-graft-poly (Acrylamide) superabsorbent polymer composites - Shafinaz Jamaludin; Shahrir Hashim (Universiti Kebangsaan Malaysia, 2011)
The development on a class of technologically advanced materials like superabsorbent polymer composites (SAPC) involved multidisciplinary research started when its potential is recognized. Oil palm empty fruit bunch-graft-poly (acrylamide) (OPEFB-g-PAAm) SAPC was synthesized via simultaneous crosslinking and graft copolymerization of acrylamide (AAm) monomer onto OPEFB backbone with N,N’-methylenebisacrylamide (MBA) and ammonium persulphate (APS) acts as crosslinker and initiator, respectively, along with neutralization using solution polymerization method. Systematically, variables that affect the swelling behaviors of OPEFB-g-PAAm SAPC were optimized. The effects of initiator, crosslinker and filler concentration as well as solvent quantity and the degree of neutralization on water absorbency of OPEFB-g-PAAm SAPC were studied. Maximum absorbency of OPEFB-g-PAAm SAPC was achieved at 589.06 g/g when the amount of APS and MBA were 1.5 wt.% and 0.15 wt.%, respectively, and the OPEFB loading was at 10 wt.%. The optimum amount of solvent used was 15 mL and the degree of neutralization was 20%. The chemical structure of the OPEFB-g-PAAm SAPC was characterized by means of Fourier transform infrared (FTIR) spectroscopy. A mechanism pathway in synthesizing OPEFB-g-PAAm SAPC was suggested